Validation of a biomarker panel in Barrett's esophagus to predict progression to esophageal adenocarcinoma. Issue Volume 31:Issue11(2018) (3rd April 2018) - Eluri, S; Klaver, E; Duits, L C; Jackson, S A; Bergman, J J; Shaheen, N J
SUMMARY: In a prior study, baseline mutational load (ML) predicted progression to high-grade dysplasia (HGD) or esophageal adenocarcinoma (EAC) in Barrett's esophagus (BE) with an area under the curve (AUC) of 0.95. We aimed to validate the test characteristics of this predictive biomarker panel using crude DNA lysates in a larger well-characterized cohort. We performed a nested case-control study of BE patients from three tertiary referral centers in the Netherlands. Cases had baseline nondysplastic BE (NDBE) and developed HGD/EAC ≥ 2 years later. Controls were matched 2:1, had baseline NDBE, and no progression. Polymerase chain reaction (PCR)-based mutational analysis was performed on crude lysates from formalin-fixed, paraffin-embedded tissue. ML was calculated from loss of heterozygosity (LOH) and microsatellite instability (MSI) at 10 genomic loci. Receiver operator characteristic (ROC) curves were created to assess the diagnostic utility of various cutoffs of ML for progression. Of 159 subjects, 58 were progressors and 101 were nonprogressors, there was no difference in mean ML in preprogression tissue in progressors and nonprogressors (ML = 0.73 ± 0.69 vs. ML = 0.74 ± 0.61, P = 0.93). ROC curves showed poor discrimination of ML in predicting progression with AUC of 0.50 at ML ≥ 1. AUC did not vary with different ML cut-points. The utility of the ML to stratify BE patients for risk of progression was not confirmed in this study. The etiology for discrepancies between this and prior studies showing high predictiveness is likely due to the use of crude lysates in this study, but requires further investigation.